Sejarah dan Perkembangan Orang Melayu di Riam Panjang Kalimantan Barat - Yusriadi Yusriadi (The Pontianak State Institute of Islamic Studies, 2014)
This article provides description of the social history and dynamics in Muslim community of Riam Panjang, a Muslim village in the Interior of Kapuas Hulu, West Kalimantan. Riam Panjang Village and the Malay people in that Village have gone through drastic changes since the 1970s. There were two periods of significant physical changes; the period prior to the 1990s, and after the 1990s. Between the two periods, it was marked with the road construction across the South in the 1990s that connects Pontianak – Sintang – Putussibau. The road has brought changes to the village. The old village was abandoned and the residents began to to form new settlements. Houses built in the new residential area have also changed. The road is also encouraging the mobility of people, making them very open. There are 4 periods in a long process of social change in Riam Panjang: the 1970s when the community members still lived in the fields, the late 1980s when they began to settle down, the 1990s when they began to come into contact with development especially the construction of the road, and the 2000s when the global cultural hegemony started to shift the local culture. Some forms of local wisdom were gone with the change.